2016
DOI: 10.21276/ijlssr.2016.2.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Halophilic Bacteria from Sundarban Soil

Abstract: ABSTRACT-Halophiles, the most predominant organisms found in the mangrove forest, include varied genera of halophilic bacteria in different environment such as salt lakes, saline soils and salted food. The majority of halophilic microorganisms studied so far produce compounds with great potential in industrial process and they have physiological properties which facilitate its use with commercial aims. In this study of Sunderban soil, focus has been made on the isolation of halophilic organisms and their chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…MS harbored higher CFU of actinomycetes, oligotrophs, sulfuroxidizing bacteria, and nitrifiers which showed a positive response to available phosphorus (AP), urease, and soil pH. Alkaline pH and higher AP in MS primarily favored the growth of these microbes (Bandyopadhyay and Sarkar, 1987;Das et al, 2011;Halder et al, 2015). The present study also showed the higher CFU of phosphate-solubilizing bacteria in MB compared to MS and NRRI.…”
Section: Discussionsupporting
confidence: 51%
“…MS harbored higher CFU of actinomycetes, oligotrophs, sulfuroxidizing bacteria, and nitrifiers which showed a positive response to available phosphorus (AP), urease, and soil pH. Alkaline pH and higher AP in MS primarily favored the growth of these microbes (Bandyopadhyay and Sarkar, 1987;Das et al, 2011;Halder et al, 2015). The present study also showed the higher CFU of phosphate-solubilizing bacteria in MB compared to MS and NRRI.…”
Section: Discussionsupporting
confidence: 51%
“…The maximal humid situation of upstream in comparison to the downstream provides variations in the fungi pollens that also changes the physio-chemical soil texture for a long time period [90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. Sundarban river delta is also an example of this largest deltoid soil microbial activity [104,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121].…”
Section: Ganga-brahmaputra-meghna Delta (Gbm)mentioning
confidence: 99%